Communication About Chronic Pain in Older Persons' Social Networks: Study Protocol of a Qualitative Approach - Merminod, Gilles; Weber, Orest; Vaucher, Carla; Semlali, Imane; Terrier, Anamaria; Decosterd, Isabelle; Rubli Truchard, Eve; Singy, Pascal (Frontiers in Public Health, 2021)
A lack of social relations appears to impact health and life expectancy among the older persons. The quality and diversity of social relations are correlated with good health and well-being in later life. Chronic pain is a crucial issue in aging population. Effective communication between the older persons with chronic pain, their relatives and the actors of the healthcare system facilitates the management of this condition. Studies on communication in later life generally do not consider the older persons’ social network as a whole, focusing only a specific segment (e.g. family or medical staff). This lack of scientific data prevents the actors of the healthcare system from offering solutions to bridge clinically relevant communication gaps. As a consequence, our study has three objectives: (1) to identify how the older persons perceive communication about chronic pain with their social network; (2) to identify their unmet communication needs; (3) to develop recommendations that improve communication about chronic pain in later life. The study will be divided into two phases. The first phase will meet objectives 1 and 2. It will involve individual interviews with about 50 people over 75 years old suffering from chronic pain and without major cognitive or auditory troubles. In this phase, we will apply a multi-layered analysis. We will map the older persons’ personal network and identify their communication practices and needs, by combining content and discourse analysis with social network theories. The second phase of the study will aim at recommendations based on the results of the first phase (objective 3). It will require focus groups with different sets of stakeholders (older persons, relative caregivers, health professionals, decision-makers). In the second phase, we will use content analysis to pinpoint the concerns and suggestions for action. The results will be disseminated on three levels: (1) to the scientific world (specialists in the field of health and aging and health communication); (2) to health practitioners working with older persons; (3) to society at large, with a focus on institutions and groups directly concerned by the issue.